Independent Financial Audit of the Financial Statements of Pension Funds Under the Conditions of Digitalization - Natchkova, Maia (Research Papers, 2022)
The main task of the Certified public accountants, registered auditors in the conditions of the global health crisis, caused by the declared pandemic by COVID 19 is to carry out an independent financial audit of the financial statements of pension funds in digital conditions so as to preserve the main purpose and tasks of audit. To express adequately their audit opinion and to protect themselves against frauds, deviations and bad audit practices in digital conditions by using new approaches, procedures, methods, rules and auditing standards that do not violate the introduced quality standards by International Standards on Auditing (IAS) and the International Code of Ethics for Professional Accountants. As a result of globalization, the new international regime for regulating pension activity and the changed national requirements of state insurance supervision, in the context of the global health crisis there is a need for registered auditors to develop a new, digitalized methods, as well as a new methodology for conducting independent financial audit of the financial statements of the pension funds.
Keywords: Pension funds; Financial statements; Digitization; Independent financial audits